Harmonization between Islamic Law and Science: DNA Test of Paternity as a Case Study Pengharmonian diantara Undang-undang Islam dan Sains Ujian Paterniti DNA Sebagai Kajian Kes - Haneef, Sayed Sikandar Shah (Journal of Islam in Asia (E-ISSN 2289-8077), 2015)
Abstract DNA testing of paternity has emerged as a conclusive scientific evidence of ascertaining paternity to overcome the problem of ‘paternity fraud’ and ‘misattributed paternity’ in the West. To harmonize it with old established common law principles of ‘presumption of paternity` and ‘ex parte’ judgment for granting a woman her claim that her bastard child belongs to a certain accused, the Western legal system has accommodated it within its law of evidence. In Islamic law, on the other hand, its reception as conclusive evidence in establishing or negating paternity is a matter of controversy among the jurists. Some have approved it partially others advocate its wholesale adoption. This presents another interesting case for the issue of harmonization between Islam and science. In this divided juridical landscape, therefore, a selective approach to evidence and proof would regard it in total harmony with Islamic law. But this approach will not only be questionable on methodological grounds but also polemical in terms of social acceptability. This paper argues for regulated proof-based approach to address its harmonization with Islamic law. Keywords: DNA Paternity Test, harmonization, Proof-Based Approach. Abstrak Ujian paterniti DNA telah muncul sebagai bukti saintifik muktamad yang menentukan paterniti untuk mengatasi masalah ’penipuan paterniti’ dan ‘paterniti salah’ di Barat. Untuk mengharmonikannya dengan undang-undang yang wujud yang berprinsip ‘paterniti andaian` dan penghakiman secara ‘ex parte’ bagi memberikan seorang wanita tuntutannya bahawa anak luar nikah itu kepunyaan tertuduh tertentu, sistem undang-undang Barat telah menempatkannya dalam undang-undang sebagai bukti. Di sisi lain, dalam undang-undang Islam, penerimaan bukti sebagai muktamad dalam menetapkan atau menafikan paterniti adalah suatu perkara yang berkontroversi di kalangan ulama. Ada yang meluluskan sebahagiannya dan yang lain menyokong penggunaan sepenuhnya. Ini merupakan satu lagi kes yang menarik bagi isu pengharmonian antara Islam dan sains. Dalam landskap perundangan terbahagi ini, pendekatan yang terpilih bagi keterangan dan bukti akan menganggap ia selaras dengan undang-undang Islam. Tetapi pendekatan ini bukan sahaja akan diragui atas alasan metodologikal tetapi juga polemik dari segi penerimaan sosial. Kajian ini menegaskan pendekatan berasaskan bukti dikawal selia untuk menangani pengharmoniannya dengan undang-undang Islam. Kata Kunci: Ujian Paterniti DNA, Pengharmonian, Pendekatan berasaskan bukti..